3. THE PREVALENCE AND RISK FACTORS FOR ORAL CANDIDIASIS IN HIV/AIDS PATIENTS AT THE CENTER FOR TROPICAL DISEASES, NGHE AN GENERAL FRIENDSHIP HOSPITAL (2022-2024) (Vietnam Journal of Community Medicine, 2024)
Objectives: The study aims to describe the prevalence and related factors for oral candidiasis in HIV/AIDS patients.Methods: Descriptive and analytical research method was employed.Results: Among 393 HIV/AIDS inpatients and outpatients undergoing clinical examination and testing, the prevalence of oral candidiasis in HIV/AIDS patients was 10.7% (42/393). Factors related to oral candidiasis included: Number of dental cleanings: [9,057: 1,205- 68,075, p < 0,05]; Wearing dentures: [15.104:2.840-80.339, p < 0.01]; Inpatient treatment: [1.197:3.855 – 37.140, p < 0.01]; and HIV/AIDS stage: [8.363:2.217 – 31.552, p < 0.01].Conclusions: The prevalence of oral candidiasis in HIV/AIDS patients was 10.7%. Oral hygiene, HIV/AIDS stage, denture wearing, and inpatient treatment were associated with oral candidiasis.
Keywords: HIV/AIDS; oral; candidiasis